Mechanism and quantitative traceability of anomalous outflow of unloaded gas from protective layer mining under complex tectonics - Xuexi CHEN; Xingyu CHEN; Jiaying HU; Aitao ZHOU; Jian XIAO; Jihong SUN; Zhilong YAN (Meitan xuebao)
Protective layer mining is an effective technical means for the prevention and control of gas disasters. The issue of abnormal water inrush during the mining process is a significant threat to the safe production of mines. This study takes the 21313 working face of Xiangshan Coal Mine as the research object, and realizes the fine inversion of gas geology of the 21512 working face based on the numerical modeling of geostatistics. By coupling simulation analysis of FLAC3D-COMSOL under complex structural stress, the mechanical evolution law and stress relief and permeability enhancement mechanism of protective layer mining are studied. The study explores the law of gas migration and gas outburst in the coal seam and adjacent seams after mining, and combines on-site statistics, carbon isotope testing, and numerical simulation for comparative analysis to achieve quantitative traceability of abnormal water inrush. Targeted measures such as stress relief and interception of the floor with directional long drilling and extraction are taken. The results show: When the protective layer working face advances from 40 m to 200 m, the depth of plastic damage of the floor increases from 8.5 m to 25 m, the maximum vertical stress rises from −19.09 MPa to −29.17 MPa, and the maximum stress release rate increases from 62% to 100%, indicating that as the advance distance increases, the coal and rock strata are significantly damaged by mining, and the floor rock mass fractures develop and connect to the No. 5 coal seam, with the stress relief range and degree continuously increasing. After mining 200 m, it is calculated that the strike stress relief angle of the protective layer is 66°, and the dip stress relief angle is 62°, and the permeability of the No. 5 coal seam roof is approximately 600 times that of the original coal seam, with obvious stress relief and permeability enhancement effect. As the advance distance of the protective layer working face increases, the range and extent of gas pressure reduction increase. The maximum gas pressure in the coal seam and adjacent seams decreases by 3.7% and 19.4% respectively after mining for 90 days; while the total gas outburst increases with the increase of the advance distance, the proportion of absolute gas outburst in the adjacent layer gradually increases. When advancing to 200 m, the proportion of absolute gas outburst in the adjacent layer is 63.00%. The comprehensive use of on-site statistical data, carbon isotope test results, and numerical simulation methods for comparative analysis shows that the proportion of gas sources from the goaf and the upper corner area remains basically stable as the working face advances, and the gas mainly comes from the adjacent layer. The average proportion of gas from the adjacent layer in the goaf and the upper corner area is 77.99% and 49.33% respectively, and the gas outburst obtained by numerical simulation is slightly greater than the measured gas outburst, and the proportion of gas outburst from the adjacent layer is less than the measured value, and the growth trend of the two is consistent. After taking precise control measures for stress relief gas, the extraction rate of stress relief gas is 55.80% and 55.01%, the wind exhaust gas volume of the working face decreases by at least 62.06%, and the concentration of methane in the return air flow decreases by at least 52.38%. The gas control effect of the protective layer working face and the protected layer is obvious, and the comprehensive precise control of gas in multiple coal seams in complex structural mining areas has been achieved.